Faktor-faktor yang mempengaruhi akuntansi konservatif - Faisal, Muhammad Faisal Arif; Hala, Yusriadi; Anwar, Anwar; Hasanah, Nur (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
The research objective examines the effect of the level of financial difficulty, profitability, growth opportunities, and managerial ownership on conservative accounting in Manufacturing Sector Companies on the Indonesia Stock Exchange. This study uses quantitative research methods. Data collection using secondary data in the form of annual financial reports accessed through the site www.idx.co.id. The population of this study was 172 companies, the sampling technique was purposive sampling method. The sample was obtained from 164 companies that have been tested for classical assumptions, namely the normality test, multicollinearity test, and heteroscedity test. Multiple linear regression data analysis method. The results showed that the level of financial difficulty, profitability, and managerial ownership had an effect on conservative accounting while growth opportunities had no effect on accounting conservatism.